Adoption of the "How are we doing?" tool by the Peruvian Service for Natural Protected Areas to enable more equitable co-management of 76 protected areas - CGIAR Research Program on Policies, Institutions, and Markets (2021)
With PIM/FTA support, CIFOR collaborated with multi-stakeholder fora in Peru and Indonesia to develop a tool that allows participants to reflect on the processes and progress of their fora so that more equitable processes and outcomes may emerge. Partnering with Peru’s Service for Natural Protected Areas (SERNANP), CIFOR adapted this tool for implementation by the multi-stakeholder management committees of 76 protected areas covering 15% of Peru’s territory. In 2021, the tool was included in SERNANP’s official guidebook for management committees.